Pengaruh Kesadaran Beragama, Kualitas Konten, dan Kesadaran Merek pada Loyalitas Produk Personal Care: Studi pada Konsumen Muslim Muda di Supermarket Tiptop Rawamangun - Marsanda Ajeng Az Zahra; Diana Sari (Jurnal Pajak dan Analisis Ekonomi Syariah, 2025)
In the modern retail era, halal personal care products are increasingly in demand among Muslim consumers, particularly young generations. This study aims to analyze the influence of religious awareness, content quality, and brand awareness on consumer loyalty, with purchasing behavior as a mediating variable. The research employed a quantitative approach using survey data collected from 150 Muslim consumers aged 18–35 who had purchased halal personal care products at Tip Top Supermarket Rawamangun, Jakarta. Data analysis was conducted with Structural Equation Modeling (SEM) using the Partial Least Square (PLS) method via SmartPLS 4.0. The results show that religious awareness, content quality, and brand awareness significantly affect purchasing behavior and consumer loyalty. Furthermore, purchasing behavior mediates the relationship between these three independent variables and loyalty. These findings highlight that loyalty among young Muslim consumers is not formed instantly, but through the integration of religiosity, credible and engaging content, and strong brand awareness, which together drive consistent purchasing behaviort.